Morphological variation of the soleus muscle: Determining general patterns and characteristics of the connective tissue architecture - Keanna Theobalt; Miles Turk; George Kalu; Robert Steele; Charles B. Withnell (Elsevier, 2024)
Background: The tendons within the soleus muscle are commonly utilized to delineate location of injury for soleus muscle strains. Strains within the soleus frequently involve the myotendinous (MTJ) or myofascial (MFJ) junctions, although spatial relationship between these tendinous structures are not well understood. This study aimed to structurally identify the MTJs and MFJs within the soleus as a starting point to understanding the distribution of connective tissue for further anatomical classification. Methods: Forty (n = 40) soleus muscles, representing left and right sides from twenty (n = 20) formalin-embalmed cadavers (average age 78 years old; 10 males, 10 females) were dissected in-situ to analyze the distribution and orientation of the MTJs and MFJs within classified morphological variants. Muscles were cut in cross-section at three measured locations, proximal, middle, and distal, which allowed for analyzation of tendons through the course of the muscle. Additionally, anterior surfaces of morphological variants were visualized and reconstructed in three dimensions using a handheld blue light 3D scanner. Results: The study revealed five morphological variants. Bipennate-Midline (n = 25), Bipennate-Medial Deviation (n = 6), Bipennate-Lateral Deviation (n = 3), Unipennate (n = 3), and Hypopennate (n = 3). Muscles included an anterior aponeurosis that was split into medial and lateral components, with each side made up of interconnections between the MTJ and MJF. The average width of the medial aponeurosis was greatest in the middle location, while the average lateral aponeurotic width decreased from proximal to distal. Regression analysis at the middle location revealed that 65 % of the change in width of the medial aponeuroses is due to the width of the medial MFJ. Conclusions: Proximal-to-distal interconnections between the lateral and medial anterior aponeuroses and their corresponding MTJs and MFJs likely play a role in soleus injury patterns, especially in morphological variants. Awareness of anatomical variations in the location and orientation of these tendinous relationships is crucial for understanding lesions on diagnostic imaging.